Computational thermo-fluid dynamics : in materials science and engineering - Nikrityuk, Petr A. (Wiley-VCH, 2011)
Combining previously unconnected computational methods, this monograph discusses the latest basic schemes and algorithms for the solution of fluid, heat and mass transfer problems coupled with electrodynamics.